Body composition measured by computed tomography is associated with colorectal cancer survival, also in early-stage disease. (2nd July 2020) - Shirdel, Mona; Andersson, Fredrick; Myte, Robin; Axelsson, Jan; Rutegård, Martin; Blomqvist, Lennart; Riklund, Katrine; van Guelpen, Bethany; Palmqvist, Richard; Gylling, Björn
Abstract: Background: Cachexia and sarcopenia are associated with poor survival after colorectal cancer (CRC) diagnosis. Computed tomography (CT) can be used to measure aspects of cachexia including sarcopenia, myosteatosis and the amount of subcutaneous and visceral adipose tissue. The aim of this study was to relate CT-based body composition variables with survival outcomes in CRC. Material and methods: In this population-based, retrospective cohort study, CT scans of 974 patients with pathological stages I–IV CRCs, collected at or very near diagnosis (years 2000–2016), were used to measure cross-sectional fat and muscle tissue areas. Body composition variables based on these measurements were assessed in relation to tumor stage and site and cancer-specific survival in stages I–III CRC ( n  = 728) using Cox proportional hazards models and Kaplan–Meier estimators. Results: Sarcopenia was associated with decreased cancer-specific survival, especially in patients with stages I–II tumors. The hazard ratio (HR) for the lowest versus highest tertile of skeletal muscle index (SMI) was 1.67; 95% confidence interval (CI), 1.08–2.58 for all stages, and HR 2.22; 95% CI 1.06–4.68, for stages I–II. Myosteatosis was also associated with decreased cancer-specific survival [(HR 2.03; 95% CI 1.20–3.34 for the lowest versus the highest tertile of skeletal muscle radiodensity (SMR)]. SMI and SMR were lower in patients with right-sided CRC, independent of age and sex. No adipose tissue measurement was significantly associated with cancer-specific survival. Conclusion: In concordance with previous studies, sarcopenia and myosteatosis were associated with decreased cancer-specific survival. The strong association between sarcopenia and poor cancer-specific survival in early-stage disease could have clinical implications for personalizing therapy decisions, including nutritional support.